Analytical compressive stress–strain model for high-strength concrete confined with cross-spirals. (15th April 2016) - West, Jonathan; Ibrahim, Ahmed; Hindi, Riyadh
Highlights: Proposed stress–strain model for high-strength concrete confined with cross-spirals. Dissimilar behavior was observed using cross-spirals in concrete confinement. The proposed model gave reasonably good prediction of the experimental results. The model predicts the concrete compressive strength confined with cross-spirals. Abstract: The behavior of high-strength concrete members subjected to seismic loads is mainly based on the ultimate strength of concrete and its ductility. The ductility of reinforced concrete is defined by both axial stresses and strains, which could be represented by the total amount of energy that concrete can absorb before failure. Conventional spiral confinement increases the nominal compressive axial capacity of concrete due to the confinement action of the concrete core, which consequently provides increase in the crushing (failure) strain. The pitch (spacing) of spiral reinforcement has a significant effect on increasing the amount of energy that concrete can absorb. This paper presents a stress–strain model for the prediction of the confined compressive strength of high-strength concrete subjected to axial stress. The stress–strain model is based on confining concrete using cross-spirals. The main parameters were the spiral spacing, and the confinement technique either conventional or cross spirals. The model is based on the results of twenty-one high-strength reduced scale concrete columns that were tested under concentric compressive axial load. The proposed model was compared with two existing models where showed good agreement with the experimental results.